Uptake and dissipation of metalaxyl-M, fludioxonil, cyantraniliprole and thiamethoxam in greenhouse chrysanthemum. (February 2020) - Gong, Wenwen; Jiang, Mengyun; Zhang, Tingting; Zhang, Wei; Liang, Gang; Li, Bingru; Hu, Bin; Han, Ping
Abstract: Production of chrysanthemum ( Dendranthema grandiflora ) in greenhouses often requires intensive pesticide use, which raises serious concerns over food safety and human health. This study investigated uptake, translocation and residue dissipation of typical fungicides (metalaxyl-M and fludioxonil) and insecticides (cyantraniliprole and thiamethoxam) in greenhouse chrysanthemum when applied in soils. Chrysanthemum plants could absorb these pesticides from soils via roots to various degrees, and bioconcentration factors (BCFLS ) were positively correlated with lipophilicity (log K ow ) of pesticides. Highly lipophilic fludioxonil (log K ow  = 4.12) had the greatest BCFLS (2.96 ± 0.41 g g −1 ), whereas hydrophilic thiamethoxam (log K ow  = −0.13) had the lowest (0.09 ± 0.03 g g −1 ). Translocation factors (TF) from roots to shoots followed the order of TFleaf  > TFstem  > TFflower . Metalaxyl-M and cyantraniliprole with medium lipophilicity (log K ow of 1.71 and 2.02, respectively) and hydrophilic thiamethoxam showed relatively strong translocation potentials with TF values in the range of 0.29–0.81, 0.36–2.74 and 0.30–1.03, respectively. Dissipation kinetics in chrysanthemum flowers followed the first-order with a half-life of 21.7, 5.5, 10.0 or 8.2 days for metalaxyl-M, fludioxonil, cyantraniliprole and thiamethoxam, respectively. Final residues of these four pesticides, including clothianidin (a primary toxic metabolite of thiamethoxam), in all chrysanthemum flower samples were below the maximum residue limit (MRL) values 21 days after two soil applications each at the recommended dose ( i.e., 3.2, 2.1, 4.3 and 4.3 kg ha −1, respectively). However, when doubling the recommended dose, the metabolite clothianidin remained at concentrations greater than the MRL, despite that thiamethoxam concentration was lower than the MRL value. This study provided valuable insights on the uptake and residues of metalaxyl-M, fludioxonil, cyantraniliprole and thiamethoxam (including its metabolite clothianidin) in greenhouse chrysanthemum production, and could help better assess food safety risks of chrysanthemum contamination by parent pesticides and their metabolites. Graphical abstract: Image 1 Highlights: Uptake and dissipation of four pesticides in greenhouse chrysanthemum were studied. Root bioconcentration factors were positively related to pesticide lipophilicity. Root-to-shoot translocation factors followed the order of leaf > stem > flower. A main toxic metabolite of thiamethoxam (clothianidin) showed greater health risks.